The Role of the Family in Promoting Emotional and Social Learning in Children in Light of Societal Transformations (A Study on Jordanian Families) - Al-Khalidi, Mariam (Journal of Ecohumanism, 2025)
This study focuses on the role of Jordanian families in encouraging emotional and social learning among children in the context of transformations that have taken place in contemporary society. A set of 200 parents from various regions of Jordan was selected to take part in the study, and the data were collected using a structured questionnaire that was designed to measure family emotional support, social learning practices, and the effect of a changing society on parenting. The results showed that Jordanian families showed a high degree of support for emotional learning (M = 4.13), especially in listening, encouraging children's emotional expression, and giving reassurance when children are emotionally distressed. Social learning was also learnt at a high level (M = 4.02), with families showing a strong degree of modelling respectful behavior, cooperation, and positive communication, with moderate levels of support regarding both supporting children's independent conflict resolution and participation in social activities. Societal transformations were rated as having a moderate to high impact on parenting (M = 3.97), with digital technology, social media, and work pressures rated as the biggest challenges that affect family patterns of interacting. Overall, the results highlight that although Jordanian families continue to provide a solid foundation for children's emotional and social development, swift societal changes present new pressures that the family must adapt to, and for which Government policies can be advantageous. The study recommends more family-centred programs and educational initiatives to help parents foster the children's emotional and social competencies in contemporary changes within society.